Continuous and rapid production of three-dimensional woven fabric preforms using a new weaving technique. (10th March 2020) - Yang, Hyunjoon; Sung, Minchang; Yang, Jewook; Song, Bohyun; Han, Heung-Nam; Yu, Woong-Ryeol
Abstract: A new manufacturing method has been developed to fabricate three-dimensional (3D) woven fabric preforms. The new method can solve problems such as delamination and fiber buckling in composites, which are known disadvantages of two-dimensional (2D) laminated fabric-reinforced composites. The new 3D weaving equipment allows for continuous and rapid production of 3D woven fabric preforms with various 3D structures. We conducted 3D modeling of the resulting fabric structures to assess the capability of the new method and the machinery involved therein. We manufactured 3D woven carbon fiber-reinforced composites using the 3D fabric preforms and epoxy resin via the resin transfer molding process. The internal architecture of the 3D composites was evaluated using micro-computed tomography and compared to the 3D modeling results; it was confirmed that 3D fabric preforms with the desired structure can be manufactured successfully by adjusting the weaving conditions of our novel weaving machine.